What might explain today's conflicting narratives on global inequality? - Martin Ravallion (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
How unequal is the world today? Is global income inequality falling, as many economists claim, or is it rising, as one often hears? This paper reviews the arguments and evidence. A number of concerns about the underlying data are identified, with biases going in both directions. Conceptual issues further cloud the picture. The claim that global inequality has been falling since 1990 can be defended for a subset of the admissible parameter values, but only a subset. Global inequality is found to be rising if one or more of the following conditions holds: (i) one attaches a high ethical weight to the poorest; (ii) one has a strong ethical aversion to high-end inequality; (iii) one takes a nationalistic perspective, emphasizing relative deprivation within countries; or (iv) one sees inequality as absolute rather than relative. Popular debates on this topic would benefit from greater clarity on the concepts used, and greater awareness of data limitations.
Keywords: D31; D63; O15; 330; global inequality; measurement; household surveys; axioms; growth